2011
DOI: 10.1111/j.1399-3062.2011.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

Infection with Klebsiella pneumoniae carbapenemase (KPC)‐producing K. pneumoniae in solid organ transplantation

Abstract: Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae is spreading globally and represents a challenge in infection control and treatment. Solid organ transplant (SOT) recipients are especially at risk for infection by multidrug-resistant bacteria, and little is known about infection with KPC-producing organisms in this setting. The aim of this study was to describe the clinical and microbiologic aspects of KPC-producing K. pneumoniae infections in SOT recipients. A KPC-2-producing K. pneumoniae ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
110
3
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(123 citation statements)
references
References 21 publications
6
110
3
4
Order By: Relevance
“…(25) . Other authors have identifi ed 26.3% of UTIs to be caused by K. pneumoniae carbapenemase-producing strains in renal transplant patients (26) . One study performed in an Italian teaching hospital over 7 months demonstrated an increase in multi-resistant bacteria strains; in the samples that showed K. pneumoniae, the urinary tract was the most frequent infection site (27) .…”
Section: Methodsmentioning
confidence: 99%
“…(25) . Other authors have identifi ed 26.3% of UTIs to be caused by K. pneumoniae carbapenemase-producing strains in renal transplant patients (26) . One study performed in an Italian teaching hospital over 7 months demonstrated an increase in multi-resistant bacteria strains; in the samples that showed K. pneumoniae, the urinary tract was the most frequent infection site (27) .…”
Section: Methodsmentioning
confidence: 99%
“…Reported mortality rates among SOT recipients with CRE infection generally range from 30-50%, and post-transplant CRKP infections have been associated with as much as a 10-fold risk of death. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] However, a more recent cohort of 164 SOT recipients across 15 international sites confirmed that while CRE infection typically occurs in the early post-transplant period, the one-year survival rate of patients who developed CRE infection within the first year of transplant was 72%. 34 While CRKP infections remain the most common type of CRE infection in SOT recipients, infections due to carbapenem-resistant Enterobacter spp., as well as NDM-and OXA-48-producing K. pneumoniae have also been reported.…”
mentioning
confidence: 99%
“…19 The incidence of post-SOT CRKP infection varies considerably by center and type of transplant (Table 1). [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] In general, CRKP infections occur early after transplant, with most studies reporting a median time of <50 days from transplant to infection. Reported mortality rates among SOT recipients with CRE infection generally range from 30-50%, and post-transplant CRKP infections have been associated with as much as a 10-fold risk of death.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 The limited amount of clinical data currently prevents definite conclusions on the eligibility of patients with end-stage liver disease and persistent CRKP carriage for transplantation. 10 Nevertheless, we propose that specifically in a CRKP outbreak situation (which implies a high risk of progression to fatal infection), these patients should not be considered for LT. 3 Thilo Busch, Ph.D. 3 Joachim M€ ossner, M.D., Ph.D. 4 Michael Bartels, M.D., Ph.D. 5 Udo X. Kaisers, M.D., Ph. The data are presented as means and standard deviations.…”
mentioning
confidence: 99%